Respuesta :
3(x + 3y + 2x − y) = 3(3x + 2y)
= 9x + 6y
See if any of these match an answer option.
= 9x + 6y
See if any of these match an answer option.
Use distributive property, and simplify like terms.
3(x + 3y + 2x - y)
= 3(x) + 3(3y) + 3(2x) + 3(-y)
= 3x + 9y + 6x - 3y
= 9x + 6y
Therefore, 9x + 6y is equal to 3(x + 3y + 2x - y)
Also, 9x + 6y can be factored into 3(3x + 2y).
3(3x + 2y)
= 3(3x) + 3(2y)
= 9x + 6y
So this pair is equivalent: 3(3x + 2y) and 9x + 6y
3(x + 3y + 2x - y)
= 3(x) + 3(3y) + 3(2x) + 3(-y)
= 3x + 9y + 6x - 3y
= 9x + 6y
Therefore, 9x + 6y is equal to 3(x + 3y + 2x - y)
Also, 9x + 6y can be factored into 3(3x + 2y).
3(3x + 2y)
= 3(3x) + 3(2y)
= 9x + 6y
So this pair is equivalent: 3(3x + 2y) and 9x + 6y